A trip around the sun : turning your everyday life into the adventure of a lifetime - Batterson, Mark. (Grand Rapids, Michigan : Baker Books, 2015)
"Mark and Dick challenge readers to shake off fear, dream big, and quit living as if the purpose of life is to arrive safely at death. The accumulated wisdom from their combined 117 trips around the sun radiates from every ... page, invigorating those of us who have found ourselves stuck in a rut dug by our sense of duty and our fear of the unknown. Anyone who wants to grab life and squeeze every ounce of joy out of it will be inspired by this unapologetic celebration of the life Jesus died to give us"--Amazon.com.
For the love of risk -- Accumulate experiences -- The original adventure -- The preposition that will change your life -- Who is more important than what -- Stepping stones -- Shared goals -- The locus of love -- Invaluable and irreplaceable -- Holy and happy -- Playing for keeps -- Never a dull moment -- The five-and-a-half-inch world between your ears -- Books with skin covers -- Learn as if you'll live forever -- Success is succession -- Reverse mentoring -- Fully alive -- Lineage and legacy -- Two thumbs up.
Includes bibliographical references.
Keywords: Christian life